2013
DOI: 10.1016/j.ejmech.2013.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel substituted pyrrolo[1,2-a]quinoxaline derivatives as inhibitors of the human protein kinase CK2

Abstract: a b s t r a c tHerein we describe the synthesis and properties of substituted phenylaminopyrrolo[1,2-a]quinoxalinecarboxylic acid derivatives as a novel class of potent inhibitors of the human protein kinase CK2. A set of 15 compounds was designed and synthesized using convenient and straightforward synthesis protocols. The compounds were tested for inhibition of human protein kinase CK2, which is a potential drug target for many diseases including inflammatory disorders and cancer. New inhibitors with IC 50 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…These compounds have been reported as key intermediates for the assembly of several heterocycles including antipsychotic agents, anti-HIV agents, adenosine A 3 receptor modulators 19 , antiparasitic agents [20][21][22][23][24][25] and antitumor agents [26][27][28][29][30] . In the course of our work devoted to discover new compounds employed in the antiparasitic chemotherapy, we previously identified some series of substituted pyrrolo[1,2-a]quinoxaline derivatives designed as interesting bioactive isosteres of quinoline derivatives [20][21][22][23][24] .Thus, taking into account our experience in the field of the synthesis of new antimalarial heterocyclic compounds based on our pyrrolo[1,2-a]quinoxaline heterocyclic core [20][21][22][23][24][27][28][29][30] , we decided to incorporate a benzyl group in position 4 of the heterocyclic skeletonof our previously described bispyrrolo [1,2-a]quinoxalines C 20 to broaden the structural diversity of these derivatives, and mainly to increase the aromatic surface of these designed compounds ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been reported as key intermediates for the assembly of several heterocycles including antipsychotic agents, anti-HIV agents, adenosine A 3 receptor modulators 19 , antiparasitic agents [20][21][22][23][24][25] and antitumor agents [26][27][28][29][30] . In the course of our work devoted to discover new compounds employed in the antiparasitic chemotherapy, we previously identified some series of substituted pyrrolo[1,2-a]quinoxaline derivatives designed as interesting bioactive isosteres of quinoline derivatives [20][21][22][23][24] .Thus, taking into account our experience in the field of the synthesis of new antimalarial heterocyclic compounds based on our pyrrolo[1,2-a]quinoxaline heterocyclic core [20][21][22][23][24][27][28][29][30] , we decided to incorporate a benzyl group in position 4 of the heterocyclic skeletonof our previously described bispyrrolo [1,2-a]quinoxalines C 20 to broaden the structural diversity of these derivatives, and mainly to increase the aromatic surface of these designed compounds ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…Jean Guillon et al have reported on the synthesis and properties of a new class of substituted phenylaminopyrrolo[1,2-a]quinoxalinecarboxylic acid derivatives, found to be potent inhibitors of the human protein kinase CK2 [41]. The work details the design and synthesis of 15 selected compounds, the latter utilising remarkably simple procedures.…”
Section: Development Of New Compounds From Commonly Available Reagentsmentioning
confidence: 98%
“…1c) form the foundation for design of a multitude of biologically active compounds. This is due to the fact that research has shown pyrrolo [1,2-a]quinoxalines to be promising starting systems for development of human CK2 protein kinase inhibitors [41]. V. A. Mamedov and A.…”
Section: Alkaloids and Their Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…[410][411] Quinoxalines are very important compounds due to their wide spectrum of biological activities such as anticancer, [412][413] antibacterial 414 and activity as kinase inhibitors. 415 It was reported that the Kaupp and co-workers (Scheme 122). 419 The yields were quantitative and the solid state reaction gave pure crystalline products just by milling stoichiometric mixtures of the crystalline reagents.…”
Section: Quinoxalinesmentioning
confidence: 99%